UPAYA MENINGKATKAN KEMAMPUAN GURU DALAM MENGAJAR MELALUI PEMBELAJARAN INTERAKTIF BERBASIS VISUAL DI SERANG BANTEN - Erly Krisnanik; Tri Rahayu; Yulnelly Yulnelly (LPPM UPN Veteran Jakarta, 2018)
Paud Assibyan and Paud KBK HI Kuntum Mekar are one of the Paud located in the Baros Serang Banten District. Their learning system still uses conventional learning media. This is because the limited facilities and infrastructure and the Paud teacher do not understand using ICT to support the learning process. Lack of knowledge of the Paud teacher using ICT in the learning process has an impact on students to become out of focus in the lesson and children easily get bored with class activities. The purpose of the community service program carried out by the authors in the Baros sub-district of Serang Banten Regency is: 1) to improve the teaching knowledge of teachers for Paud children using ICT; and 2) improve the quality of children's learning while playing, independence, creative and innovative by utilizing visual media. This PKM activity involves various PAUD managers and higher education institutions as a form of community service. The method used for community service activities is through a constructive and visual approach between us as a lecturer and PAUD teachers. The expected results are that teachers begin to use ICT as one of the interactive learning media for their students.